Okronosisli bir olguda omurga ankilozu - (:unkn) unknown (My University, 2003)
Yirmi yıldır devam eden bel ağrısı şikayeti ile başvuran 39 yaşlındaki erkek hastanın servikal ve torakolumbar grafilerinde, disklerde yaygın kalsifikasyon ve ankiloz gözlendi. Burun çevresi ve kulaklarda mavi-gri pigmentasyon gelişen hastada okronosisten şüphelenildi. idrarda homogentisik asit düzeyinin normalden yüksek olması ve alkali ortamda idrar renginin siyahlaşması üzerine okronosis tanısı kondu. Kronik bel ağrısı, direkt grafide intervertebral disklerde yaygın kalsifikasyon, ankiloz ve dokularda siyah-gri pigment birikimi olan hastalarda ayırıcı tanıda okronosis de düşünülmelidir.

A thirty-nine-year-old man presented with a complaint of low back pain with a history of 20 years. Cervical and thoracolumbar radiographs showed wide calcification areas and ankylosis in the intervertebral discs. Observation of blue-gray pigmentation around his nose and ears suggested a diagnosis of ochronosis, which was confirmed by the detection of high levels of homogentisic acid in the urine and dark urine color following alkalization. Ochronosis should be included in the differential diagnosis in patients with chronic low back pain, calcified intervertebral discs, and black pigmentation in cartilagenous and collagenous tissues.
Ankylosis of the spine in a case with ochronosis
Keywords: Tıbbi Araştırmalar Deneysel